Hyperbranched Polymers for Biomedical Applications - Bandyopadhyay, Abhijit; Sengupta, Srijoni; Das, Tamalika (Springer Series on Polymer and Composite Materials, 2018)
This book presents a comprehensive study on a new class of branched polymers, known as hyperbranched polymers (HBPs). It discusses in detail the synthesis strategies for these particular classes of polymers as well as biocompatible and biodegradable HBPs, which are of increasing interest to polymer technologists due to their immense potential in biomedical applications. The book also describes the one-pot synthesis technique for HBPs, which is feasible for large-scale production, as well as HBPs' structure-property relationship, which makes them superior to their linear counterparts.   The alterable functional groups present at the terminal ends of the branches make HBPs promising candidates in the biomedical domain, and the book specifically elaborates on the suitable characteristic properties of each of the potential biological HBPs' applications. As such, the book offers a valuable reference guide for all scientists and technologists who are interested in using these newly developed techniques to achieve faster and better treatments.